2001
DOI: 10.1046/j.1526-100x.2001.009001049.x
|View full text |Cite
|
Sign up to set email alerts
|

Common Reed Phragmites australis: Control and Effects Upon Biodiversity in Freshwater Nontidal Wetlands

Abstract: Phragmites australis (common reed) has expanded in many wetland habitats. Its ability to exclude other plant species has led to both control and eradication programs. This study examined two control methods-herbicide application or a herbicide-burning combinationfor their efficacy and ability to restore plant biodiversity in non-tidal wetlands. Two Phragmites -dominated sites received the herbicide glyphosate. One of these sites was burned following herbicide application. Plant and soil macroinvertebrate abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 27 publications
3
111
0
Order By: Relevance
“…As noted previously, P. australis is able to colonize wetlands quickly and produce large patches, which can displace resident wetland plants (Ailstock et al, 2001;Trebitz and Taylor, 2007;Tulbure and Johnston, 2010;Whyte et al, 2008). The wide range of disturbances and environmental variables that P. australis can tolerate, coupled with its morphological characteristics, contribute to P. australis having a competitive advantage over many resident wetland plant species.…”
Section: Effects On Vegetation Communitiesmentioning
confidence: 78%
See 1 more Smart Citation
“…As noted previously, P. australis is able to colonize wetlands quickly and produce large patches, which can displace resident wetland plants (Ailstock et al, 2001;Trebitz and Taylor, 2007;Tulbure and Johnston, 2010;Whyte et al, 2008). The wide range of disturbances and environmental variables that P. australis can tolerate, coupled with its morphological characteristics, contribute to P. australis having a competitive advantage over many resident wetland plant species.…”
Section: Effects On Vegetation Communitiesmentioning
confidence: 78%
“…Supporting this hypothesis, Gagnon Lupien et al (2015) attribute their finding that P. australis had no severe effect on bird use in southwestern Quebec marshes to the early stage of invasion in their study system. As P. australis expands, replacing meadow marsh and cattail marsh, it smooths and elevates substrate, filling in small holes and open-water pools through litter accumulation (Weinstein and Balletro, 1999;Windham and Lathrop, 1999), reducing floral diversity, and creating dense stands of stiff stems (Ailstock et al, 2001;Schummer et al, 2012;Windham, 2001). These changes alter marsh habitat making it less heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic and terrestrial plants support animal communities that differ from those of unvegetated sediments, and often differ across plant species (e.g., Moon 1934;Brodersen 1995;Radomski and Goeman 2001;Romanuk and Levings 2003;Salovius and Kraufvelin 2004;Kraufvelin and Salovius 2004). Consequently, invasions of alien plants frequently not only push out native plants but also change associated animal communities (e.g., Ailstock et al 2001;Strayer et al 2003). Predation by terrestrial predators (birds and mammals) may be so intense that it reduces the density of aquatic prey near the water's edge by direct consumption or intimidation (Power 1984;Power et al 1989;Burlakova and Karatayev 2007).…”
Section: Biological Interactionsmentioning
confidence: 99%
“…7 Plant community studies in the P. australis dominated ecosystems have shown that Phragmites are not conducive to the establishment of other plant species and that colonization of disturbed wetland areas by this plant usually ensures the development of dense stands. [8][9][10][11] The present review is mainly focused on the discussion of the various mechanisms by which P. australis exerts its invasive behavior to successfully colonize and replace the native biodiversity.…”
Section: Introductionmentioning
confidence: 99%